2020
DOI: 10.1016/j.firesaf.2020.103012
|View full text |Cite
|
Sign up to set email alerts
|

CFD study of fire-induced pressure variation in a mechanically-ventilated air-tight compartment

Abstract: Computational Fluid Dynamics (CFD) simulations of fire-induced pressure and ventilation flow in a mechanically-ventilated air-tight compartment, representative of a passive house, are presented. Experiments conducted by University of Mons are used to assess the results. The simulation heat release rate is prescribed based on experimental measurements. The experimental duct flow rate is about 80 m 3 /h. Two methods are used to meet the aforementioned value in simulations: 1) by modeling the actual fan curve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The results illustrated that the pressure rise is an important issue to be considered in air-tight compartment fires. The over-pressures were also reported in simulation results [4,5,[7][8][9][10][11], which match well with experiments. A more detailed summary of fire-induced pressure build-up studies can be found in Ref.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results illustrated that the pressure rise is an important issue to be considered in air-tight compartment fires. The over-pressures were also reported in simulation results [4,5,[7][8][9][10][11], which match well with experiments. A more detailed summary of fire-induced pressure build-up studies can be found in Ref.…”
Section: Introductionsupporting
confidence: 81%
“…8, where, the LEAK FO, LEAK AO and LEAK FA indicate the leakage from the fire room to the outside, the leakage from the adjacent room to the outside and the leakage from the fire room to the adjacent room through the gap at the bottom of the partition door, respectively. The leakage flow rate is dependent on the pressure difference and the leakage area [18]: (11) where is the leakage volume flow rate (m 3 /s), is the leakage area (m 2 ), is the pressure difference between the adjacent zones (Pa) and is the ambient air density (kg/m 3 ). Thus, the leakage flow rate has the same trend as the pressure variation.…”
Section: Leakage Flow Ratementioning
confidence: 99%
“…This revival of interest has led to the need for revisiting compartment fire with up-to-date research tools, both for experimental and numerical studies. Topics regarding pressure variations, extinction phenomena, and instabilities have been recently addressed [3], [4], [5], [6], [7], [8]. Among these studies, one of importance is the issue concerning reduced-scale modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded over-pressures range from 100 Pa to 1650 Pa in the fire experiments within 50 s from ignition [12]. On top of the experimental research, numerical studies also demonstrate the behavior of fire-induced pressure variations and assess the capability of Computational Fluid Dynamics (CFD) tools (e.g., Fire Dynamics Simulator, FDS) in predicting the fire-induced pressure variations [17,18]. Although this phenomenon has attracted attention, there is still a lack of systematic research on the factors that affect the fire-induced pressure variations, as well as a lack of experimental data for the validation of numerical results.…”
Section: Introductionmentioning
confidence: 95%